Paths to power : how insiders and outsiders shaped american business leadership / by Anthony J. Mayo, Nitin Nohria and Laura G. Singleton - Mayo, Anthony J. (Boston, 2006)
Who made it to the top of Corporate America in the twentieth century? And what do their experiences mean for the next generation of business leaders? In "Paths to Power", Anthony J. Mayo, Nitin Nohria, and Laura G. Singleton answer these questions. The authors explore access to business leadership opportunities showing how a small group of "insiders" possess advantages that facilitate a smooth journey to the top while a larger group of "outsiders" face disadvantages that make their path to leadership positions more difficult. Yet throughout the history of American business, the composition of insiders and outsiders has shifted. Examining data on leader birthplaces, religious affiliation, education, socioeconomic status, race, and gender, "Paths to Power" explains how the demographics of leadership have changed over the 20th century and how they're changing now. Further, they discuss the mechanisms of advancement for insiders and outsiders, and show how these mechanisms have also evolved. Though white men still hold most power positions in business, the authors assert that the gates of access aren't as static as they seem.
Keywords: Executives-United states-History